1988
DOI: 10.1152/ajpcell.1988.255.1.c102
|View full text |Cite
|
Sign up to set email alerts
|

Different physiological signatures of sweat gland secretory and duct cells in culture

Abstract: Human eccrine sweat gland cells grown in culture were found to lose their characteristic shape, becoming flattened and organized into multilayers. The resting membrane potentials of the cultured secretory cells (-35 +/- 2 mV, n = 36) were significantly higher than those measured for cultured duct cells (-22 +/- 1 mV, n = 58, P less than or equal to 0.01). When the cholinergic agonist methacholine (10(-5) or 10(-6) M) was administered, the cultured secretory cells could be distinguished unequivocally by their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 2 publications
1
16
1
Order By: Relevance
“…The presence of cholera toxin in the culture medium, in the latter report (Jones et al 1988), might explain a missing isoprenaline response in that particular study. Cholera toxin is known to stimulate adenylate cyclase by ADP ribosylating the a-subunit of N., a modification-that inhibits agonist-stimulated GTPase, resulting in a stabilization of N. in the GTPbound active conformation and persistent activation of adenylate cyclase (Cassel & Selinger, 1977;Ross & Gilman, 1980).…”
Section: Discussionmentioning
confidence: 71%
“…The presence of cholera toxin in the culture medium, in the latter report (Jones et al 1988), might explain a missing isoprenaline response in that particular study. Cholera toxin is known to stimulate adenylate cyclase by ADP ribosylating the a-subunit of N., a modification-that inhibits agonist-stimulated GTPase, resulting in a stabilization of N. in the GTPbound active conformation and persistent activation of adenylate cyclase (Cassel & Selinger, 1977;Ross & Gilman, 1980).…”
Section: Discussionmentioning
confidence: 71%
“…Whether the cultures derive from whole glands, coils or ducts the pharmacological phenotype appears to be the same; virtually all the SCC and that stimulated by agonists appears to be due to electrogenic sodium absorption, based upon the high specificity of amiloride in the micromolar range. Some amiloride sensitive cells have been detected in the primary cultures of secretory coil (Jones et al, 1988) (Hashimoto et al, 1982). Thus far there are no reports of cultured epithelia with a coil-like phenotype, although recently a sweat gland cell line, NC1-SG3, was described (Lee & Dessi, 1989) which did not respond to amiloride; unfortunately neither did the cultures respond to cholinoceptor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al developed a repeated shearing method that allowed the rapid isolation of intact viable human sweat glands from skin samples, in which it was possible to easily distinguish and separate coil and ductal portions of the human gland to examine individual functions of those regions separately . Explanting glands, coils or ducts in tissue culture, including permeable supports, generated experimental material that allowed the investigation of normal and CF glands using electrophysiology and biochemical techniques . These experiments further revealed that cholinergic and adrenergic agonists could induce transmonolayer anion fluxes expected from secretory cells, suggesting that the cultured monolayer presented a model for understanding the cellular physiology of the intact secretory coil.…”
Section: Cell Culturementioning
confidence: 99%